Status of Human-Wildlife Conflict and Assessment of Crop Damage by Wild Animals in Gaurishankar Conservation Area, Nepal - Awasthi, Bairam; Singh, Nanda Bahadur (Journal of Institute of Science and Technology, 2015)
This study tries to explore the status of Human-Wildlife Conflict (HWC) within the Gaurishankar Conservation Area (GCA), Nepal. The maximum damage of maize (39%) and potato (30%) crops were reported due to wildlife in the study area. Major wildlife pests were monkey, porcupine, goral, barking deer, jackal and Himalayan black bear. About ninety five percent of respondents reported crop damage problem was increasing in the area after GCA establishment. Fair and quick disbursement of compensation for crop loss and regular monitoring of the wild animal needed to be adopted to reduce human-wildlife conflicts. Change in cropping and crop composition, particularly cultivation of high value medicinal plants were also suggested. The findings suggest participatory approach to manage problematic animal species in GCA. Journal of Institute of Science and Technology, 2015, 20(1): 107-111